Business Incubation and its Role in the Creation of Entrepreneurs in South Kalimantan - Herry Azhar Pradana; Dewi Siska (Nusantara Science and Technology Proceedings, 2022)
The creation of new entrepreneurs in the City of Banjarmasin and South Kalimantan Province is one of the missions of the local government as a commitment to encourage more people to start a business in the region. The Local Government took the initiative to develop a Business Incubator (Kawal Incubator and Inbitek Borneo Incubator) as a medium for developing and creating new and more focused entrepreneurs. This Study aims to analyze the role of business incubation in creating new entrepreneurs for 90 tenants from Kawal Incubator and 40 tenants from Inbitek Borneo. This research uses descriptive qualitative research with the Reflective, Recursive Design and Development Model (R2D2) model. Currently, the local community (Kalsel Creative Forum) manages a business incubation run by the City of Banjarmasin, while Inbitek Borneo is managed in-house. The Study shows that Full Stack Incubation Services are needed; legal facilitation, photo product, Business Logo, Digital Marketing, Funding opportunities (Credits and Grants), and access to the market. The Funding scheme provided by the government is too rigid to match the dynamism of business incubators; it requires more flexible financing. The incubation model also determines the success of the creation of new entrepreneurs, especially in the recruitment process, selection of mentors and mentors, curriculum, and program escalation.